STAT3 modulates cigarette smoke-induced inflammation and protease expression - Geraghty, Patrick; Wyman, Anne E.; Garcia-Arcos, Itsaso; Dabo, Abdoulaye J.; Gadhvi, Sonya; Foronjy, Robert (Frontiers in Physiology, 2013)
Signal transducer and activator of transcription-3 (STAT3) regulates inflammation, apoptosis and protease expression, which are critical processes associated with airway injury and lung tissue destruction. However, the precise role of STAT3 in the development of airway diseases such as chronic obstructive pulmonary disease (COPD) has not been established. This study shows that cigarette smoke activates STAT3 in the lungs of mice. Since cigarette smoke activated STAT3 in the lung, we then evaluated how the loss of STAT3 would impact on smoke-mediated lung inflammation, protease expression and apoptosis. STAT3+/+ and STAT3-/- mice were exposed to eight days of cigarette smoke. Compared to the STAT3+/+ mice bronchoalveolar lavage fluid (BALF) cellularity was significantly elevated in the STAT3-/- mice both before and after cigarette smoke exposure, with the increase in cells primarily macrophages. In addition, smoke exposure induced significantly higher BALF protein levels of Interleukin-1α (IL-1α), and monocyte chemotactic protein-1 (MCP-1) and higher tissue expression of keratinocyte chemoattractant (KC) in the STAT3-/- mice. Lung mRNA expression of MMP-12 was increased in STAT3-/- at baseline. However, the smoke-induced increase in MMP-10 expression seen in the STAT3+/+ mice was not observed in the STAT3-/- mice. Moreover, lung protein levels of the anti-inflammatory proteins SOCS3 and IL-10 were markedly lower in the STAT3-/- mice compared to the STAT3+/+ mice. Lastly, apoptosis, as determined by caspase 3/7 activity assay, was increased in the STAT3-/- at baseline to levels comparable to those observed in the smoke-exposed STAT3+/+ mice. Together, these results indicate that the smoke-mediated induction of lung STAT3 activity may play a critical role in maintaining normal lung homeostasis and function.